Biomechanical Comparisons of Single- and Double-Legged Drop Jumps with Changes in Drop Height - Wang, L.-I.; Peng, H.-T. (International Journal of Sports Medicine, 2014)
The purpose of this study was to compare the biomechanics of single- and double-legged drop jumps (SDJ vs. DDJ) with changes in drop height. Jumping height, ground contact time, reactive strength index, ground reaction force, loading rate of ground reaction force, joint power and stiffness were measured in 12 male college students during SDJ from 20-, 30-, 40-, and 50-cm heights and DDJ from of 20- and 40-cm heights. The peak impact force was increased with the incremental drop height during SDJs. The jumping height and leg and ankle stiffness of SDJ30 were greater than those of SDJ40 and SDJ50. The knee and hip stiffnesses of SDJ30 were greater than those of SDJ50. The impact forces of SDJ30-50 were greater than those of DDJ40. The leg, ankle, knee and hip joint stiffnesses of SDJ20-30 were greater than those of DDJ20 and DDJ40. The propulsive forces of SDJ20-50 were greater than those of DDJ20 and DDJ40. The jumping height of SDJ30 was greater than that of DDJ20. Drop height of 30 cm was recommended during single-legged drop jump with the best biomechanical benefit. Single-legged drop jump from 20–30 cm could provide comparable intensity to double-legged drop jump from 40 cm.
Keywords: plyometric exercise; stretch-shortening cycle; landing impact; stiffness; reactive strength index